Faktor-Faktor Dan Pengukuran Cybersickness Pada Driving Simulator: Tinjauan Pustaka - Chalis Fajri Hasibuan (Jurnal Rekayasa Sistem Industri, 2023)
A driving simulator is one of the research tools used to identify the causes of traffic accidents on the highway. While driving simulators are frequently used in research, there is concern that HMD-based driving simulators may cause a side effect for the user known as cybersickness. Various factors are widely used to identify the formation of cybersickness from various virtual environments with different results on the formed cybersickness. In contrast, the factors that influence the formation of cybersickness using driving simulators using virtual reality based on HMD have not been identified whether they produce the same or different research results, so that it can make a difference in further research. The purpose of this study is to conduct a literature review of the factors used to identify cybersickness formed in the use of driving simulators using HMD-based virtual reality and the results of using these factors. The method used by searching articles from databases includes Google Scholar, Science Direct, Scopus, Springer and IEEE with relevant keywords. In the initial search, the terms 'VR sickness', 'cybersickness', 'motion sickness', 'simulator sickness', 'visually induced motion sickness', 'virtual reality', and 'driving simulator', were eliminated using the PRISMA method. Of the 653 articles obtained, 17 were analyzed regarding driving simulators using HMD-based virtual reality. The results found factors that influence the formed cybersickness, such as gender, user age, experience, user posture, duration of use, the hardware used, Field Of View (FOV), congenital diseases and time of use. Of the 17 articles analyzed, there was no difference in the results of the factors used to identify the formed cybersickness.